Theory, Method And Applications Of Deep Learning Impacts On Biomedical Application - et. al., Dr. A. Prakash , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Medical imagery allows for an increase of biological processes at genetic level in visualisation and quantitative analysis, which is of high importance for early cancer detection. Deep learning has been widely applied in recent years in medical imaging science, as it endures the limitations of visual assessment and traditional methods of machinery training by drawing hierarchical features with strong representation ability. Deep learning was proposed as a more general model, requires less data engineering and allows for more accurate prediction while working with high data volumes. We perform a review in this research on the aspects of cancer diagnosis and diagnoses that promote profound learning. Second, we outline an overall cancer detection profound learning model. Thirdly, we have checked and received input on the most current studies on cancer deep learning systems and some research perspectives.